The Enforcement of Criminal Law Against Transfer of Fiduciary Guarantee Objects based on Justice Values - Munandar, Aris; Arifulloh, Achmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
Everyone has the right to recognition, guarantee, protection and legal certainty that is fair and treated equally before the law. Law No. 42 of 1999 concerning Fiduciary Guarantees has regulated criminal sanctions and fines, but in practice there are several problems regarding law enforcement, including police investigators being unable to charge third parties who have received pledges from fiduciary recipients. Keywords: Land, Ownership Certificate, Overlapping. The purpose of this study is to provide suggestions and recommendations regarding criminal law enforcement regarding the transfer of fiduciary guarantee objects based on the value of justice. This study usessocio-legal approachas well as the legislative approach and case approach. The results of this study are law enforcement according to current regulations that the regulation of criminal sanctions against the transfer of fiduciary collateral objects as regulated in Article 36 of Law No. 42 of 1999 does not reflect the value of justice, because criminal sanctions are only imposed on debtors, while parties who enjoy the benefits of the transfer cannot be held criminally responsible. In addition, there are weaknesses in the legal substance aspect in the form of a vacuum in regulations regarding the reception of fiduciary objects, from the legal structure aspect in the form of a lack of selectivity of financing institutions and weak synergy of law enforcement officers, as well as from the legal culture aspect in the form of low public legal awareness and economic pressure.